PEMBERDAYAAN BUMDES WUKIRRAYA MELALUI PENGUATAN KAPASITAS MANAJERIAL DAN SINERGI POTENSI LOKAL DI DESA WUKIRSARI, BANTUL - Annis Nurfitriana Nihayah; Karsinah Karsinah; Dyah Maya Nihayah; Mohammad Aulia Rachman; Fauzul Adzim; Silvia Margaret; Nisrina Hanifah Santos; Intan Putri Aditria (Universitas Mataram, 2025)
Wukirsari is a village in Bantul Regency that has been declared a tourist village. As a tourist village, Wukirsari Village has received a lot of attention related to existing activities. One of them is the existence of Village-Owned Enterprises (BUMDES). BUMDes Wukirraya is a Bumdes in Wukirsari Village. Bumdes Wkirraya has great potential in developing batik craft-based businesses and cultural tourism. The problem of managerial capacity, low community participation, and minimal business diversification hamper the strategic role of BUMDes. This community service activity aims to identify the main problems faced by BUMDes Wukirraya and design institutional strengthening strategies through a participatory approach. The methods used include observation, interviews, and focus group discussions (FGD) with BUMDes managers, MSME actors, and community leaders. The results show that business management training, facilitation of collaboration between sectors, and active involvement of residents are the keys to strengthening the function of BUMDes. This activity contributes to increasing human resource capacity, entrepreneurial awareness, and the direction of business development that is more strategic and in accordance with local potential.